Analisis Determinasi Underpricing Saham pada Saat Initial public offering (IPO) di Bursa Efek Indonesia - Sudirman, Muhammad Dimas; Mona Adriana Sutrisno (PT. Cendekia Sapta Indonesia, 2026)
This study examines the influence of profitability, capital structure, firm size, underwriter reputation, public share ownership, and stock market conditions on IPO underpricing in Indonesia during the period from 2022 to 2024. It addresses a research gap by exploring the dynamics of the Indonesian capital market in the post-pandemic context, an area that has received limited scholarly attention. By incorporating both financial and non-financial variables into a comprehensive analytical model, this study provides a more integrated perspective on the determinants of underpricing. The sample comprises 84 firms selected through purposive sampling, and the data were analyzed using multiple linear regression. The findings indicate that profitability, underwriter reputation, and market conditions have a significant negative effect on underpricing, while capital structure has a significant positive effect. Firm size and public share ownership are not found to have a significant influence. These results highlight the importance of financial signals and reputational factors in shaping investor perceptions during IPO pricing. The study offers a theoretical contribution to Signaling Theory and provides empirical insights for the literature on IPOs in Indonesia in the post-pandemic period.Keywords: Initial public offering (IPO), Underpricing, Profitability, Capital Structure, Firm Size, Underwriter Reputation, Oversubscription, Public Shareholding, Stock Market Conditions.